Serial analysis of blood biomarker concentrations in dogs with pneumonia, septic peritonitis, and pyometra - Robert Goggs; Sarah N. Robbins; Denise M. LaLonde‐Paul; Julie M. Menard (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Prolonged antimicrobial drug (AMD) treatment is associated with antimicrobial resistance development. Biomarker measurement may aid treatment decision‐making. Objectives Investigate temporal changes in blood biomarker concentrations in dogs undergoing treatment for pulmonary and intra‐abdominal infections; compare time to biomarker concentration normalization with duration of clinician‐directed AMD treatment. Animals Forty‐two client‐owned dogs with pneumonia (n = 22), septic peritonitis (n = 10), or pyometra (n = 10). Methods Plasma concentrations of C‐reactive protein (CRP), serum amyloid A (SAA), haptoglobin, procalcitonin, nucleosomes, cell‐free DNA (cfDNA), high‐mobility group box‐1 (HMGB1), CC‐motif chemokine ligand‐2 (CCL2), CXC‐motif chemokine ligand‐8 (CXCL8), and keratinocyte chemoattractant‐like (KC‐Like) were quantitated in samples collected on days 1, 3, 7, 14, 28, and 60. Treatment was directed by clinicians blinded to biomarker concentrations. Results Concentrations of CCL2, CRP, and KC‐Like were maximal on D1, concentrations of SAA, cfDNA, HMGB1, and nucleosomes were maximal on D3 and haptoglobin concentrations were maximal on D7. These maximal concentrations were significantly different from those on D60. Concentrations of CRP and SAA decreased by 80% from peak and into respective reference intervals before AMDs were discontinued. For CRP, the median (interquartile range [IQR]) times to 20% peak and normal were 7 (6‐9) and 7 (6‐12) days, respectively, and for SAA they were 4 (4, 5) and 6 (5‐8) days, respectively, compared to a median (IQR) duration of AMD prescribing of 16 (12‐23) days (all P < .0001). Conclusions and Clinical Importance Biomarker concentrations normalized within 7 to 14 days. Serial measurements of CRP and SAA might aid identification of disease resolution and could help guide AMD prescription decision‐making.